Improving health workforce governance: the role of multi-stakeholder coordination mechanisms and human resources for health units in ministries of health - Tim Martineau; Kim Ozano; Joanna Raven; Wesam Mansour; Fiona Bay; Dominic Nkhoma; Elsheikh Badr; Sushil Baral; Shophika Regmi; Margaret Caffrey (BMC, 2022)
Abstract Background A cohesive and strategic governance approach is needed to improve the health workforce (HW). To achieve this, the WHO Global Strategy on Human Resources for Health (HRH) promotes mechanisms to coordinate HRH stakeholders, HRH structures and capacity within the health sector to support the development and implementation of a comprehensive HW agenda and regular reporting through WHO's National Health Workforce Accounts (NHWA). Methods Using an adapted HRH governance framework for guidance and analysis, we explored the existence and operation of HRH coordination mechanisms and HRH structures in Malawi, Nepal, Sudan and additionally from a global perspective through 28 key informant interviews and a review of 165 documents. Results A unified approach is needed for the coordination of stakeholders who support the timely development and oversight of an appropriate costed HRH strategy subsequently implemented and monitored by an HRH unit. Multiple HRH stakeholder coordination mechanisms co-exist, but the broader, embedded mechanisms seemed more likely to support and sustain a comprehensive intersectoral HW agenda. Including all stakeholders is challenging and the private sector and civil society were noted for their absence. The credibility of coordination mechanisms increases participation. Factors contributing to credibility included: high-level leadership, organisational support and the generation and availability of timely HRH data and clear ownership by the ministry of health. HRH units were identified in two study countries and were reported to exist in many countries, but were not necessarily functional. There is a lack of specialist knowledge needed for the planning and management of the HW amongst staff in HRH units or equivalent structures, coupled with high turnover in many countries. Donor support has helped with provision of technical expertise and HRH data systems, though the benefits may not be sustained. Conclusion While is it important to monitor the existence of HRH coordination mechanisms and HRH structure through the NHWA, improved 'health workforce literacy' for both stakeholders and operational HRH staff and a deeper understanding of the operation of these functions is needed to strengthen their contribution to HW governance and ultimately, wider health goals.